Gambaran Hasil Procalcitonin dan D-Dimer Pada Pasien Covid-19 Di RSUD Budhi Asih Jakarta Timur - Permata, Kamilia Gulin; Nurdiani, Catu Umirestu; Nugroho, Heru Purwanto; Susanti, Ellis (Anakes : Jurnal Ilmiah Analis Kesehatan, 2024)
The World Health Organization (WHO) declared an epidemic caused by Coronavirus Disease – 19 (Covid-19) on January 9, 2020. The first case was found on December 30, 2019 in Wuhan, China. The virus spreads through droplets. Symptoms of COVID-19 start from shortness of breath, cough and fever. Patients who are confirmed with COVID-19 are then carried out laboratory tests in the form of Procalcitonin (PCT) and D-dimer. This study was conducted using a descriptive method whose data was taken from laboratory examination results for the period April 2022 - May 2023 as many as 54 PCT and D-dimer result data. The results of the frequency distribution examination were based on normal values, normal PCT levels as many as 24 patients (44%) and abnormal PCT levels as many as 30 patients (56%) and normal D-dimer levels as many as 23 patients (43%) and abnormal D-dimer levels as many as 31 patients (57%). The frequency distribution in COVID-19 patients based on gender, male as many as 28 patients (52%) while in women as many as 26 patients (48%).In this conclusion, the frequency distribution of PCT and D-dimer examinations based on gender, men are higher than women. PCT examination is more with abnormal values compared to normal values. D-dimer test results with abnormal values more than normal values. Keyword            : Covid-19, D-dimer, PCT